НАПРЯМИ ВДОСКОНАЛЕННЯ КООРДИНАЦІЇ СПІЛЬНОЇ ДІЯЛЬНОСТІ ОРГАНІВ ДОСУДОВОГО РОЗСЛІДУВАННЯ В УКРАЇНІ - Коломієць, Вадим Іванович (SUPREMANCE OF LAW, 2018)
It is argued that the fi rst step in the direction of improving the coordination of the interaction of pretrial investigation bodies is the creation of a single coordination center that will coordinate the interaction of pre-trial investigation bodies. It is emphasized that the creation of the latter will allow: to increase the effectiveness of the joint activity of pre-trial investigation bodies, and thus will contribute to the faster resolution of relevant cases; reduce the terms of investigations; to improve the quality and effectiveness of the pre-trial investigation; reduce the level of crime; increase the level of trust in law enforcement agencies. It is substantiated that an effective way to improve the coordination of the activities of pre-trial investigation bodies should be the development and adoption by the Ministry of Internal Affairs of Ukraine of a separate by-law regulatory act “Procedure for the interaction of pre-trial investigation bodies” It was established that in order to improve the coordination of pre-trial investigation bodies, it is necessary to improve the personnel support system of pre-trial investigation bodies.
Keywords: improvement; coordination; bodies of pre-trial investigation; legal regulation